Workers' compensation policy and reforms in Western Australia - Guthrie, Rob (John Curtin Institute of Public Policy, 2007)
In Western Australia for at least the last decade workers compensation legislation has been a focus of Government and stakeholder attention. Those stakeholders include workers, employers, government and insurers as well as a range of associated service providers. Following the election of the Labor Government in 2001 considerable attention was placed on the revision of laws passed by the previous Coalition Government. The latter had been heavily influenced by the apparent need to reduce compensation system costs for employers and insurers and many of the legislative changes instituted by the Coalition were made at the expense of common law rights for workers. Whilst this trend has been entirely reversed by the Gallop/Carpenter Labor Governments there is evidence that all stakeholders in the system have been considered more fully in Labor policy development and subsequent legislative reforms which have eventuated in a more balance approach to the compensation system.